Analysis of Factors Affecting Profit Quality in Timber and Processing Sub-Sector Companies Listed on the Indonesia Stock Exchange - Nilam Sari; M Rimawan (INVOICE : JURNAL ILMU AKUNTANSI, 2023)
Profit information is one of the most important parts of financial reports that attracts a lot of attention from investors, because investors tend to choose to invest in companies that experience an increase in profits every year. This research aims to analyze the influence of profitability, leverage, company size and Investment Opportunity Set (IOS) on earnings quality. The sampling technique used was using a saturated sampling technique. The sample in this research is 4 companies in the wood and processing sub-sector that have been listed on the Indonesia Stock Exchange (BEI) from 2019 to 2021. The data in this study was processed using the SPSS version 26 application with the multiple linear regression analysis method. The hypothesis testing method uses a significance level of 5% or 0.05. The research results show that 1) the profitability variable has no effect on earnings quality, 2) the leverage variable has an effect on earnings quality, 3) the company size variable has no effect on earnings quality, and 4) the investment opportunity set variable has an effect on earnings quality. From this research, the results obtained show that the variables profitability, leverage, company size and investment opportunity set have a simultaneous influence on earnings quality. Partially, the profitability and company size variables have no effect on earnings quality, while the leverage and investment opportunity set variables have an effect on earnings quality.